Program Latihan Mindfulness Untuk Menurunkan Stres Lansia Dengan Diabetes Melitus di Desa Jumerto, Kecamatan Patrang, Kabupaten Jember - Suryaningsih, Yeni; Zulka, Ayesie Natasa; Budi, Putri Ayu; Faizatu, Kharisma (Indonesian Journal Publisher, 2023)
Partners' health problems include the increasing problem of Diabetes Mellitus which causes a lot of stress for the elderly, and the absence of an activity program to reduce stress for the elderly in Jumerto village. The mindfulness training program is an exercise program developed to reduce stress and reduce the occurrence of health problems experienced by the elderly caused by psychological disorders. This program was developed in line with the Muhammadiyah University of Jember's service strategic plan and government policies related to elderly health care. This program works with the elderly posyandu in Jumerto Village, Patrang District, Jember Regency. The targets and outcomes resulting from this community service program are 1) service products in the form of knowledge and mindfulness training for the elderly with Diabetes Mellitus and posyandu cadres, 2) the availability of simple modules or books about the physical and mental health of the elderly with Diabetes Mellitus, 3) articles that national accreditation. The methods that will be used to achieve this goal are 1) mentoring, 2) education and 3) practice of mindfulness exercises in the elderly with Diabetes Mellitus and elderly Posyandu cadres with an evaluation of the process and results of the mindfulness training program activities. The mindfulness training program was carried out from April 24 -May 16 2023 every Saturday at the Jumerto Village Hall, Patrang District, Jember Regency, and was attended by 45 elderly people. Activities carried out include socialization of activities, screening of the physical and mental health of the elderly and mindfulness exercises. The results of the process evaluation carried out on 45 elderly people participating in the mindfulness training program were carried out by facilitators accompanied by 2 elderly cadres and 2 nurses starting on April 24 2023. The results evaluation was carried out on May 16 2023 and found 100% of the elderly expressed satisfaction with the mindfulness program at Posyandu Elderly with proven patients with Diabetes Mellitus Most of them experience mild stress (66.6%). So that this program can be continued by the Elderly Posyandu